Hayley Williams’ Shout-Out on the Farro Brothers’ Leaving as Seen in "Fast In My Car", "Now", "Grow Up", "Interlude: Moving On", "Interlude: I’m not Angry Anymore", and "Future" - Surawira Lintang Ningtyas (Lexicon, 2012)
This graduating paper attempts to examine Williams' writing about moving forward and growing up based on the six song-lyrics taken from the Paramore album after the leaving of its two founding members, guitarist Josh and drummer Zac Farro. These six song-lyrics present a theme of future and maturity despite the hardships that Williams experienced before the Farro brothers‟ leaving.This graduating paper applies Abrams‟ expressive approach to study the author’s feelings through the song-lyrics written by Williams. To support the whole analysis, a library research is conducted, supported with articles, interviews, videos, magazines, e-magazines, the album itself, and reliable websites.The result of the analysis shows that Williams deals with the Farro brothers’ leaving on Paramore in a more positive way. After all the anger, disappointment, and hardships, Williams proves herself to not let these negativities take over her life and how life is too short to be angry.